The Impact of Known Heart Disease on Long‐Term Outcomes of Catheter Ablation in Patients with Atrial Fibrillation and Left Ventricular Systolic Dysfunction: A Multicenter International Study. (8th February 2016) - PRABHU, SANDEEP; LING, LIANG‐HAN; ULLAH, WAQAS; HUNTER, ROSS J.; SCHILLING, RICHARD J.; McLELLAN, ALEX J.A.; EARLEY, MARK J.; SPORTON, SIMON C.; VOSKOBOINIK, ALEX; BLUSZTEIN, DAVID; MARIANI, JUSTIN A.; LEE, GEOFFREY; et al.
The Impact of Known Heart Disease on AF Ablation Outcomes: Background: Catheter ablation for AF is an effective treatment for patients with AF and systolic LV dysfunction; however, the clinical outcome is variable. We evaluated the impact of cardiomyopathy etiology on long‐term outcomes post‐catheter ablation. Methods: Patients undergoing AF ablation across 3 centers (2 Australian, 1 UK) from 2002 to 2014, with LVEF<45% were evaluated. Patients were stratified into those with known heart disease as a cause of cardiomyopathy (KHD), and those with idiopathic dilated cardiomyopathy (IDCM). Results: One hundred and one patients (IDCM = 77, KHD = 24) with AF and LVEF <45% underwent AF ablation. The KHD group (ischemic HD in 67%) were older (61 ± 7 vs. 55 ± 11 years, P = 0.005), with a higher CHADS2 score (2.0 ± 0.8 vs. 1.6 ± 0.7, P = 0.016), but otherwise well matched. After mean follow‐up of 36 ± 23 months, AF control was greater in the IDCM group (82% vs. 50% in KHD, P < 0.001). On multivariate analysis IDCM was associated with long‐term AF control (P = 0.033). The IDCM group had less functional impairment at follow‐up (NYHA class 1.5 ± 0.7 vs. 2.0 ± 0.8, P = 0.005) and improved LVEF (50 ± 11% vs. 38 ± 10%, P < 0.001). Super responders (EF improvement >15%) were overwhelmingly in the IDCM group (94% vs. 6%, P < 0.001) with greater AF control (89% vs. 61%, P < 0.001). All‐cause mortality was significantly higher in the KHD group (17% vs. 1.3%, P = 0.002). Conclusion: IDCM was associated with greater AF control, and improvement in symptoms and LVEF compared to patients with KHD post‐AF ablation. AF is an important reversible cause of HF in patients with an unexplained CM and catheter ablation an effective treatment option.